One woman's choice - Waring, Rob (Australia : Heinle, Cengage Learning, 2009)
Flora Salonik, a woman who lives in a tiny village with the Dorobo people of East Africa, must decide if she can let go of her previous life in the city
'National geographic' - cover
Book is accompanied by one DVD, entitled'One woman's choice' bearing the same call number and available at Bahagian Koleksi Media
Keywords: English language -- Textbooks for foreign speakers